Output-Based Event-Triggered Model Predictive Control for Networked Control Systems*. Issue 1 (July 2017) - Berkel, Felix; Watkins, Benjamin; Liu, Steven; Görges, Daniel
Abstract: In this paper an output-based model predictive controller for linear time-invariant discrete-time networked control systems subject to constraints is studied. In the networked control system the control loop is closed over a communication network between sensor and controller as well as controller and actuator. An output-based controller using a Luenberger observer for reconstruction of the system state is designed. For both communication networks event-triggers are utilized to reduce the communicational burden. Recursive feasibility of the control law is provided by robust control methods. Moreover, asymptotic stability of the closed-loop system is guaranteed. A simulation example illustrates that the proposed method can reduce the network utilization significantly.